Perturbation of the carbon cycle during the late Pliensbachian – early Toarcian: New insight from high-resolution carbon isotope records in Morocco. (April 2016) - Bodin, Stéphane; Krencker, Francois-Nicolas; Kothe, Tim; Hoffmann, René; Mattioli, Emanuela; Heimhofer, Ulrich; Kabiri, Lahcen
Abstract: Preceding the early Toarcian Oceanic Anoxic Event by ∼1 Myr, the Pliensbachian–Toarcian boundary event is in many aspects as severe and disturbing for the environment as its better-studied successor. Both events are associated with rapid and pronounced global warming, major faunal and floral turnover, increased hydrological cycling and dramatic collapses of carbonate production. To better characterize the Pliensbachian–Toarcian boundary event, a high-resolution, paired carbonate and organic matter carbon isotope survey of three sections from the Central High Atlas Basin of Morocco has been undertaken. A pronounced negative shift in the carbonate carbon-isotope record, not paralleled by a similar excursion in the organic carbon, can be linked to the collapse of the neritic carbonate factory in the earliest Toarcian. These results show that, contrary to the Toarcian Oceanic Anoxic Event, a rapid and massive injection of 13 C-depleted carbon into the atmosphere is not responsible for the environmental perturbations observed during the Pliensbachian–Toarcian boundary event. However, input of isotopically non-depleted carbon such as mantle source CO2 into the atmosphere as a potential cause for the Pliensbachian–Toarcian boundary event cannot be excluded. This would most probably be sourced from an early pulse of the Karoo–Ferrar Large Igneous Province. Graphical abstract: Highlights: High-resolution carbon isotope records from three sections in Morocco. Decoupling between δ 13 Ccarb and δ 13 Corg at the Pliensbachian–Toarcian boundary. Negative shift of δ 13 Ccarb linked to massive neritic carbonate demise event.